ANALISIS KANJI JUKUJIKUN DALAM MANGA KIMETSU NO YAIBA - Gina Purnamasari; Hety Nurohmah (WIDAI Japanese Journal, 2022)
This research is entitled The Analysis of Jukujikun in Manga Kimetsu no Yaiba. The aim of this research is to describe the process of kanji jukujikun form contained in the manga Kimetsu no Yaiba and to identify the relationship of form meaning of kanji jukujikun. This manga of Kimetsu no Yaiba Vol. 6-8 was used in obtaining the data. The process theory of kanji jukujikun form used was the theory of Todo (1986:74), and the theory of relations in meaning of kanji jukujikun used was Tsuchiya’s (1986:58). The type of the research used was descriptive qualitative. The methods used in collecting the data in this study were observation and note-taking methods. The analysis method used was referential match. Furthermore, the presentation used in data analysis was informal presentation. The result of this research indicated that there were 12 data from the process of forming eight data with the giver relation, and two data with matched relation, one data with certainty relation, and one data with the subject predicate relation. From the relationship of the format meaning based on the combination of two kanji that belonged to the fourth structure, there was seven data, and the one that belonged to the seventh structure, therein lied one data. Moreover, based in the combination of three kanji that belonged to the first structure, there was one data, and the ones that belonged to the third structure had three data.